Successive interference cancellation receiver algorithms for uplink STBC coded MC-CDMA systems - ZENG Yan-xing; YIN Qin-ye; DENG Ke; DENG Jian-guo (Tongxin xuebao)
A QR decomposition based and a minimum mean square error （MMSE） based successive interference cancel-lation receiver algorithms were proposed for the uplink of space-time block coded multi-carrier code division multiple access （MC-CDMA） systems. As the processed data matrix preserved the orthogonal structure of space-time block code, the sub-optimum decoding could be achieved via simple linear processing. Compared with the traditional zero-forcing （ZF） receiver algorithm, the proposed algorithms avoid the enhancement of white noise power at the receiver. Simulation results demonstrate the proposed algorithms outperform the ZF receiver algorithm in both independent and correlated fading channels and they require 4 dB less signal-to-noise ratio than the traditional one for a bit error rate of 10?6.